Redescription of the Chinese ninespine stickleback, Pungitius sinensis (Guichenot 1869) (Gasterosteiformes, Gasterosteidae) - Matsumoto, Tatsuya; Matsuura, Keiichi; Hanzawa, Naoto (Zootaxa, 2025)
The Chinese ninespine stickleback, Pungitius sinensis (Guichenot 1869) is redescribed, based on seven syntypes and 368 non-type specimens from various localities in the Far East. Pungitius sinensis is distinguished from all its congeners by the following combination of characters: dorsal-fin rays usually IX + 10 or 11; anal-fin rays usually I + 9 or 10; pectoral-fin rays usually 10; pelvic-fin rays I + 1 or 2; upper and lower procurrent caudal-fin rays usually 5 each, 10 in total; lateral plates arranged in a full or incomplete row, forming a distinct keel on side of caudal peduncle; usually 7 ventral plates on caudal peduncle; vertebrae usually 34 (15 abdominal + 19 caudal vertebrae); dorsal-fin spines inclining alternately to sides of mid-line; first dorsal-fin spine located anterodorsally to upper end of pectoral-fin base; ascending process of pelvis well-developed, upper end of pelvis reaching to level of base of fifth pectoral-fin ray; antero-ventral process of ectocoracoid present, right and left ectocoracoids articulating anteriorly with each other; a distinct ridge on cleithrum and ectocoracoid; membranes of dorsal-fin spines almost hyaline; body dark green or dark yellow. Geographic variations in number of dorsal-fin spines, pelvic-fin soft rays, and lateral plates are documented in this species. Gasterosteus wosnesenjenskyi Kessler 1876, Pygosteus steindachneri Jordan & Snyder 1901, and Gasterosteus brevispinosus Otaki 1908 are considered as junior synonyms of P. sinensis.